2002
DOI: 10.1890/0012-9615(2002)072[0151:proilt]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Parasite (Ribeiroia Ondatrae) Infection Linked to Amphibian Malformations in the Western United States

Abstract: Parasites and pathogens can influence the survivorship, behavior, and very structure of their host species. For example, experimental studies have shown that trematode parasites can cause high frequencies of severe limb malformations in amphibians. In a broad‐scale field survey covering parts of California, Oregon, Washington, Idaho, and Montana, we examined relationships between the frequency and types of morphological abnormalities in amphibians and the abundance of trematode parasite infection, pH, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
117
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(139 citation statements)
references
References 34 publications
5
117
0
6
Order By: Relevance
“…This is an important finding, as infection by R. ondatrae has been shown to cause limb malformations in anurans (e.g. Johnson et al 1999;Johnson et al 2002;Johnson and Sutherland 2003;Schotthoefer et al 2003). The exact mechanism of how the parasite induces these malformations remains unclear, though the mechanical perturbation hypothesis has been the most widely accepted to date.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…This is an important finding, as infection by R. ondatrae has been shown to cause limb malformations in anurans (e.g. Johnson et al 1999;Johnson et al 2002;Johnson and Sutherland 2003;Schotthoefer et al 2003). The exact mechanism of how the parasite induces these malformations remains unclear, though the mechanical perturbation hypothesis has been the most widely accepted to date.…”
Section: Discussionmentioning
confidence: 98%
“…This is in part due to the severe and grotesque limb/body malformations caused by infection (Blaustein and Johnson 2003;Johnson et al 1999). For example, Johnson et al (2002) reported a significant association between severe limb malformations and Ribeiroia infection in nine species of natural amphibian populations distributed across the Western USA. Within infected anurans, the majority of metacercariae (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trematode metacercariae infecting P. platensis probably mature in a bird or reptile final host. Likewise, there are several reports of amphibians acting as second intermediate hosts for trematode larvae, emphasizing the importance of these parasites in the helminth communities (Hamann and Kehr 1999;Hamann and González 2009;Hamann et al 2006), and their influence in the host fitness (Kuris 1997, Johnson et al 2002. The prevalence of digeneans is strongly associated with mollusk abundance (Lafferty 1997).…”
Section: Discussionmentioning
confidence: 99%
“…; hereafter, Ribeiroia), the chytridiomycete fungus B. dendrobatidis (hereafter, BD), and the oomycete Achlya flagellata to test for interactive effects of multiple pathogens on Pacific treefrogs (Pseudacris regilla). All three pathogens are implicated in amphibian mortality or pathology (Tiffney and Wolf 1939;Johnson et al 2002a;Berger et al 1998) and the cosmopolitan A. flagellata (Post 1987;Khulbe 1994;Noga 1996) and globally distributed BD Pearl et al 2009) are likely to co-occur extensively with Ribeiroia throughout its wide range in North America (Johnson et al 2002a.…”
Section: Introductionmentioning
confidence: 99%